2021
DOI: 10.1021/acs.est.1c00078
|View full text |Cite
|
Sign up to set email alerts
|

A New Group of Heterocyclic Nitrogenous Disinfection Byproducts (DBPs) in Drinking Water: Role of Extraction pH in Unknown DBP Exploration

Abstract: pH adjustment prior to extraction is an important step in water sample pretreatment processes for exploration of new/unknown disinfection byproducts (DBPs) in drinking water. To achieve a better extraction efficiency, the pH of a water sample is usually adjusted to a low level (e.g., < 0.5) to ensure that target DBPs are in their neutral forms. However, such a practice may elude some amphoteric DBPs (especially those nitrogenous DBPs with multiple functional groups), which can accept protons at a low pH and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…55,56 The LC 50 of eight halogenated pyridinols and two halobenzoquinones in zebrafish embryos was 8.1−373 and 4.0−5.5 μM, respectively, which are also much lower than that of THMs and HAAs. 50 However, for marine algae (Isochrysis galbana, Skeletonema costatum, Porphyridium cruentum, and Dunaliela tertiolecta), the EC 50 of 1,2,3,4,5,5-hexachloro-1,3-cyclopentadiene was 0.01−0.37 μM, 40 which is approximately 100,000× lower than that of HAAs and approximately 1800× lower than that of halophenols. In addition, the LC 50 of 1,2,3,4,5,5hexachloro-1,3-cyclopentadiene in freshwater fish and saltwater shrimp was 0.03−0.18 μM, 40 than that of THMs and HAAs and 22−12,433× lower than that of halogenated pyridinols and halobenzoquinones.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…55,56 The LC 50 of eight halogenated pyridinols and two halobenzoquinones in zebrafish embryos was 8.1−373 and 4.0−5.5 μM, respectively, which are also much lower than that of THMs and HAAs. 50 However, for marine algae (Isochrysis galbana, Skeletonema costatum, Porphyridium cruentum, and Dunaliela tertiolecta), the EC 50 of 1,2,3,4,5,5-hexachloro-1,3-cyclopentadiene was 0.01−0.37 μM, 40 which is approximately 100,000× lower than that of HAAs and approximately 1800× lower than that of halophenols. In addition, the LC 50 of 1,2,3,4,5,5hexachloro-1,3-cyclopentadiene in freshwater fish and saltwater shrimp was 0.03−0.18 μM, 40 than that of THMs and HAAs and 22−12,433× lower than that of halogenated pyridinols and halobenzoquinones.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Compared with other emerging aromatic or alicyclic DBPs reported in drinking water, the levels of HCPDs were similar to those of HBQs and chlorophenylacetonitriles 32,48 but were higher than those of halogenated pyridinols and halophenylacetamides. 49,50 Stability of HCPDs. To preliminarily assess the stability of the HCPDs and potential for hydrolysis, the two HCPDs with available standards (HEX and 1,2,3,4-tetrachloro-1,3-cyclopentadiene) were evaluated in nanopure water at pH 7 over 168 h in an incubator in the dark at 25 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nontarget analysis with a high-resolution ultra-performance liquid chromatograph/electrospray ionization-hybrid quadrupole time-of-flight mass spectrometer (UPLC/ESI-QTOF-MS) has become a commonly used method for probing unknown DBPs in drinking water. ,, However, it is widely acknowledged that nontarget analysis is considerably labor-intensive and time-consuming due to (but not limited to) the complex water matrix. To simplify the analysis in the initial stage, the replacement of real drinking water samples with chlorinated model precursor samples is regarded as a promising resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first group of DBPs, i.e., trihalomethanes (THMs), was found in 1974 [ 6 ], more than 800 DBPs belonging to various classes have been gradually determined both in real disinfection plants and in controlled laboratory tests [ 7 , 8 ]. With the development of analytical methods, it is conceivable that more DBPs will be continuously identified [ 9 , 10 , 11 , 12 ]. For example, Zhang, et al [ 13 ] recently analyzed the DBPs in ozonated wastewater, and they identified eight new Br-DBPs, including 2-bromostyrene, 2-bromo-benzaldehyde, and 2-bromophenylacetonitrile.…”
Section: Introductionmentioning
confidence: 99%